Experiences of community pharmacists involved in the delivery of a specialist asthma service in Australia - Emmerton Lynne M; Smith Lorraine; LeMay Kate S; Krass Ines; Saini Bandana; Bosnic-Anticevich Sinthia Z; Reddel Helen K; Burton Deborah L; Stewart Kay; Armour Carol L (BMC, 2012)
Abstract Background The role of community pharmacists in disease state management has been mooted for some years. Despite a number of trials of disease state management services, there is scant literature into the engagement of, and with, pharmacists in such trials. This paper reports pharmacists' feedback as providers of a Pharmacy Asthma Management Service (PAMS), a trial coordinated across four academic research centres in Australia in 2009. We also propose recommendations for optimal involvement of pharmacists in academic research. Methods Feedback about the pharmacists' experiences was sought via their participation in either a focus group or telephone interview (for those unable to attend their scheduled focus group) at one of three time points. A semi-structured interview guide focused discussion on the pharmacists' training to provide the asthma service, their interactions with health professionals and patients as per the service protocol, and the future for this type of service. Focus groups were facilitated by two researchers, and the individual interviews were shared between three researchers, with data transcribed verbatim and analysed manually. Results Of 93 pharmacists who provided the PAMS, 25 were involved in a focus group and seven via telephone interview. All pharmacists approached agreed to provide feedback. In general, the pharmacists engaged with both the service and research components, and embraced their roles as innovators in the trial of a new service. Some experienced challenges in the recruitment of patients into the service and the amount of research-related documentation, and collaborative patient-centred relationships with GPs require further attention. Specific service components, such as the spirometry, were well received by the pharmacists and their patients. Professional rewards included satisfaction from their enhanced practice, and pharmacists largely envisaged a future for the service. Conclusions The PAMS provided pharmacists an opportunity to become involved in an innovative service delivery model, supported by the researchers, yet trained and empowered to implement the clinical service throughout the trial period and beyond. The balance between support and independence appeared crucial in the pharmacists' engagement with the trial. Their feedback was overwhelmingly positive, while useful suggestions were identified for future academic trials.